BİYOLOJİK DOZİMETRİ VE İLGİLİ GELİŞMELER - COŞKUN, Münevver; COŞKUN, Mahmut (Cerrahpaşa Medical Journal, 2014)
Background.- It is inevitable to use radiation in many fields of the life at present and in future. In this respect, monitoring of the radiation has a big importance to keep of the harmful effects of radiation for human being and his future. For this purpose biological dosimeter has been used for nearly 30 years and shows improvements at the parallel of the increasing scientific developments. In this work, past and present situation of using of biological materials and cytogenetic techniques for the determination of the absorbed radiation dose were discussed. Also, especially the reasons and results of using of chromosome aberrations in the biological dosimeter have been summarized with the investigation of published papers about this subject.